A Model of Delivering Messages Related to COVID-19 to the Collective Society of Kampung Pulo in Ciliwung Riverside East Jakarta - Melati Mediana Tobing (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This article reviews the difficulties of marginalized urban communities in Jakarta when carrying out social activities in the midst of a pandemic. In fact, many urban people live by maintaining a lifestyle with their group and tend to become urban rural communities. In this community, the social group becomes the main reference and even the reference in attitude. Social restrictions are considered to be a restraint on their habits and values, so that understanding the concept of social standing is in stark contrast to their daily habits and tends to be ignored. This paper provides an overview as well as a model of the cultural communication approach in collectivistic cultured communities that exist in village communities that are widely found in a number of big cities in Indonesia. The micro-ethnogafi method was applied to informants living on the outskirts of Ciliwung Kampung Pulo, East Jakarta. This study found that when the delivery of messages about COVID-19 was carried out through a cultural approach through the role of group leaders, the residents of Kampung Pulo were willing to interact by wearing masks and maintaining a minimum distance of one meter.